Performance of Cracked Ultra-High-Performance Fiber-Reinforced Concrete Exposed to Dry-Wet Cycles of Chlorides - Longlong Niu; Shiping Zhang (Advances in Materials Science and Engineering)
This paper presents an experimental study on the performance of cracked ultra-high-performance fiber-reinforced concrete (UHPC) exposed to dry-wet cycles of 3.5% NaCl solution under the temperature of 60°C. The results show that the wider the crack, the higher the corrosion degree of steel fibers embedded in UHPC, and the deeper the chloride ion diffusion on both sides of the crack. With the increase of dry-wet cycles, the flexural strength of precracked UHPC first decreases and then increases, and the lowest flexural strength was observed in 60 dry-wet cycles. Although self-healing is hard to cease the corrosion of steel fibers, it can relieve the corrosion of steel fibers and improve the flexural strength exposed to 100 dry-wet cycles.